2009
DOI: 10.2987/08-5830.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Barrier Treatments on Native Vegetation in A Southern California Desert Habitat

Abstract: Treating perimeters with residual insecticides for protection from mosquito vectors has shown promise. These barrier treatments are typically evaluated in temperate or tropical areas using abundant vegetation as a substrate. However, there is an emerging interest to develop this technology to protect deployed US troops in extreme desert environments with sparse vegetation. We used a remote desert area in the Coachella Valley, California, to 1) evaluate bifenthrin barrier treatments on native xeric vegetation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 28 publications
1
20
0
Order By: Relevance
“…Barrier perimeters of vegetation common in most pastoral areas that are impacted by RVF can be treated with residual insecticides such as bifenthrin that has been shown to provide protection from mosquito disease vectors. 9 Treatment of artificial substrates including interior and exterior walls, suspended sheets, bed nets, and livestock fencing might be effective in controlling adult mosquito vectors of RVFV.…”
Section: Introductionmentioning
confidence: 99%
“…Barrier perimeters of vegetation common in most pastoral areas that are impacted by RVF can be treated with residual insecticides such as bifenthrin that has been shown to provide protection from mosquito disease vectors. 9 Treatment of artificial substrates including interior and exterior walls, suspended sheets, bed nets, and livestock fencing might be effective in controlling adult mosquito vectors of RVFV.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Mutinga et al (1992) showed that permethrin-impregnated wall cloth could reduce endophilic sand ßy species in Kenyan rural homes by as much as 85%. Combining ULV treatments of natural sand ßy populations, shown here to be effective, with control factors like treated wall cloths, treated vegetation (Britch et al 2009), treated camoußage netting (Britch et al 2010b), permethrintreated clothing, and use of DEET, could substantially minimize opportunities for human-sand ßy contact and thus minimize opportunities for transmission of Leishmania to deployed troops.…”
Section: Discussionmentioning
confidence: 94%
“…Historical accounts of collateral reduction of sand ßies, human cases of leishmaniasis, or both during massive pesticide campaigns against vectors of malaria indicate that residuals such as DDT can be effective (Nadim and Amini 1970). Large scale programs of applying residual pesticides other than DDT targeted against sand ßies are still used by many countries and international agencies, and by the U.S. military in Iraq and Afghanistan (Coleman et al 2006), but these programs can be difÞcult to sustain (Alexander and Maroli 2003) and should be only one element in a multifaceted system to reduce sand ßy populations and human cases of visceral and cutaneous leishmaniasis (Britch et al 2009(Britch et al , 2010a. Residual pesticide applications should be used in conjunction with aerosol applications such as ultra-low volume (ULV) pesticide dispersal (Lofgren 1970), habitat reduction such as removal of rodent burrows (Faizulin et al 1976), physical exclusion such as bed nets (Zollner et al 2007), and personal protective measures such as application of DEET to exposed skin and permethrin treatment of clothing (Coleman et al 2006; reviewed in Kitchen et al 2009) to form an integrated vector management system of defense against sand ßies.…”
mentioning
confidence: 99%
“…albopictus, has increased recently (Hubbard et al 2005, Trout et al 2007, Li et al 2010. Various other residual pyrethroid insecticides have also been tested for the same purpose (Royal 2004, Cilek and Hallmon 2006, Cilek 2008, Britch et al 2009, Doyle et al 2009, Hurst et al 2012). In most cases they have been applied as barrier treatments with an intention to prevent or reduce adult mosquitoes from penetrating into an untreated area targeted for protection (Cilek 2008, Britch et al 2009, Li et al 2010).…”
mentioning
confidence: 97%
“…Various other residual pyrethroid insecticides have also been tested for the same purpose (Royal 2004, Cilek and Hallmon 2006, Cilek 2008, Britch et al 2009, Doyle et al 2009, Hurst et al 2012). In most cases they have been applied as barrier treatments with an intention to prevent or reduce adult mosquitoes from penetrating into an untreated area targeted for protection (Cilek 2008, Britch et al 2009, Li et al 2010). However, with harborage spraying, insecticide is also applied to isolated clusters of vegetation within the community if they are suitable resting sites for peridomestic mosquitoes, and thus turning their normal resting sites into lethal zones.…”
mentioning
confidence: 99%